2001
DOI: 10.1089/109065701753617417
|View full text |Cite
|
Sign up to set email alerts
|

Factor V Leiden Mutation Screened by PCR and Detected with Lanthanide-Labeled Probes

Abstract: The Factor V Leiden mutation is an important human polymorphism, responsible for increased risk of venous thrombosis in heterozygotes as well as homozygotes. Therefore, screening is a useful possibility, and many detection systems have been described for PCR products. We have developed a simplified and robust assay using oligonucleotide probes for normal and mutant sequences, labeled with europium and samarium, respectively, and measured by time-resolved fluorescence. Populations consisting of 233 Welsh and 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Approximately 5% of Caucasians are either heterozygous carriers or homozygous for the factor V Leiden mutation; the prevalence is reported to be lower for other ethnic groups . Potter et al have developed a simplified and robust assay using oligonucleotide probes for normal and mutant factor V Leiden mutation sequences, labeled with europium and samarium, respectively, and measured by time-resolved fluorescence. The electronic array analysis of amplicons for factor V mutation by using strand displacement amplification was described. After electronic addressing of the amplicons to specific array locations, the reporter oligonucleotides modified with either Cy3 or Cy5 were added, and fluorescence at each location was quantified.…”
mentioning
confidence: 99%
“…Approximately 5% of Caucasians are either heterozygous carriers or homozygous for the factor V Leiden mutation; the prevalence is reported to be lower for other ethnic groups . Potter et al have developed a simplified and robust assay using oligonucleotide probes for normal and mutant factor V Leiden mutation sequences, labeled with europium and samarium, respectively, and measured by time-resolved fluorescence. The electronic array analysis of amplicons for factor V mutation by using strand displacement amplification was described. After electronic addressing of the amplicons to specific array locations, the reporter oligonucleotides modified with either Cy3 or Cy5 were added, and fluorescence at each location was quantified.…”
mentioning
confidence: 99%
“…Studies varied greatly in the extent to which they described the population from which the participants came; only 17 studies adequately reported the setting or population from which the blood samples were obtained [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Most described the experimental test adequately; 60 to 70% of the studies gave a detailed description of their reference methods.…”
Section: Resultsmentioning
confidence: 99%
“…Three other studies used a fluorophore probe to detect FVL [46][47][48], and all reported 100% concordance. Potter et al tested a lanthanide-labeled probe for FVL detection [19]. There was 1% discordance on the first test, and 0.26% remained discordant after repeating the test.…”
Section: Detection Of Fvlmentioning
confidence: 99%
“…Genetic diagnosis of factor V Leiden based on a heteroduplex technology (14) and PCR based methods with variously labeled primers combined with different detection/separation techniques have also been described (15,16). Even though heteroduplex-based mutation detection comprises a single PCR reaction followed by PCR product analysis, it uses either standard or capillary polyacrylamide gel electrophoresis (PAGE).…”
Section: Discussionmentioning
confidence: 99%